Prolactin rs1341239 T allele may have protective role against the brick tea type skeletal fluorosis - Li, Bing-Yun; Yang, Yan-Mei; Liu, Yang; Sun, Jing; Ye, Yan; Liu, Xiao-Na; Liu, Hong-Xu; Sun, Zhen-Qi; Li, Mang; Cui, Jing; Sun, Dian-Jun; Gao, Yan-Hui (PloS one, 2017)
Prolactin (PRL) has been reported to be associated with increased bone turnover, and increased bone turnover is also a feature of skeletal fluorosis (SF). Autocrine/paracrine production of PRL is regulated by the extrapituitary promoter and a polymorphism in the extrapituitary PRL promoter at -1149 (rs1341239) is associated with disturbances of bone metabolism in other diseases. Here, we have investigated the possibility that the rs1341239 polymorphism is associated with SF, which results from the consumption of brick tea. We conducted a cross-sectional study in Sinkiang, Qinghai, Inner Mongolia in China. Demography survey questionnaires were completed and physical examination and X-ray diagnoses were used to diagnose SF. Brick tea water fluoride intake (IF) and urinary fluoride (UF) were tested by an F-ion selective electrode method. A Sequenom MassARRAY system was used to determine PRL gene polymorphisms. Subjects who were younger than 45 years of age and carried the T allele had a significantly decreased risk of SF [OR = 0.279 (95%CI, 0.094-0.824)] compared to those carrying the homozygous G allele. This phenomenon was only observed in Kazakh subjects [OR = 0.127 (95%CI, 0.025-0.646)]. Kazakh females who carried T alleles has a decreased risk of SF [OR = 0.410 (95%CI, 0.199-0.847)]. For Kazakh subjects which IF is less than 3.5 mg/d, a decreased risk of SF was observed among the participants who carried T alleles [OR = 0.118 (95%CI, 0.029-0.472)]. Overall, subjects with 1.6-3.2 mg/L UF and carried T alleles had a significantly decreased risk of SF [OR = 0.476 (95%CI, 0.237-0.955)] compared to homozygous G allele carriers. This phenomenon was only observed in Kazakh subjects [OR = 0.324 (95%CI, 0.114-0.923)]. Our results suggested that the PRL rs1341239 T allele decreases the risk of brick tea SF.